Les vêpres siciliennes - Verdi, Giuseppe 1813-1901 (Opus Arte, 2011)
Verdi's romantic tragedy of tensions between private passions and public politics set in Sicily, in this production in the 1940s; includes the full Four Seasons ballet in Act III.